2017
DOI: 10.3174/ajnr.a5492
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Manifestations of Neurosarcoidosis: An Underrecognized Aspect of the Imaging Spectrum

Abstract: Involvement of the central nervous system by sarcoidosis, also referred to as neurosarcoidosis, is seen clinically in about 5% of patients with systemic disease. CNS involvement most frequently affects the leptomeninges and cranial nerves, though the ventricular system, brain parenchyma, and pachymeninges may also be involved. Even though the involvement of the intracranial vascular structures is well-known on postmortem studies, there is scant literature on imaging manifestations secondary to the vessel wall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
57
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 44 publications
3
57
0
2
Order By: Relevance
“…13 In this study, we found that DMVE is a common finding in neurosarcoidosis, though not as yet recognized as a distinct cerebrovascular manifestation. 5 It was significantly more common in men, consistent with cerebrovascular manifestations of sarcoidosis being more frequent in this group. 5 DMVE came to our attention owing to its conspicuity on SWI, a sequence that is now widely available and was originally developed as a means for MR venography.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…13 In this study, we found that DMVE is a common finding in neurosarcoidosis, though not as yet recognized as a distinct cerebrovascular manifestation. 5 It was significantly more common in men, consistent with cerebrovascular manifestations of sarcoidosis being more frequent in this group. 5 DMVE came to our attention owing to its conspicuity on SWI, a sequence that is now widely available and was originally developed as a means for MR venography.…”
Section: Discussionsupporting
confidence: 61%
“…5 It was significantly more common in men, consistent with cerebrovascular manifestations of sarcoidosis being more frequent in this group. 5 DMVE came to our attention owing to its conspicuity on SWI, a sequence that is now widely available and was originally developed as a means for MR venography. 14 A recent review showed 1 case with mild periatrial DMVE in a typical radial configuration on SWI; however, the presence of engorgement itself was not described.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations